2001
DOI: 10.1136/jnnp.70.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and surgical management of intraspinal synovial cysts: report of 19 cases

Abstract: Objective-Synovial cysts of the vertebral facet joints are a source of nerve root compression. DiVerent surgical procedures are in use, but no consensus has been formed so far as to which method should be used in synovial cysts. To clarify the role of surgical management, the eYcacy of operative procedures and factors influencing the outcome in our own series of 19 patients treated between 1994 and 1998 were analysed. Methods-Nineteen patients with a mean age of 65 years underwent surgery for medically intract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 16 publications
(4 reference statements)
6
84
0
2
Order By: Relevance
“…In another literature review, Shah and Lutz [42] identified 139 patients treated conservatively, out of which 47% finally received surgical treatment due to absence of sustained benefit. Similarly, Hsu et al had a success rate of 55% with conservative therapy, while in another series of treatment by corticosteroid injection the long-term success rate did not exceed 57% [3,5,45]. Furthermore, most authors reporting results of conservative treatment have rather short follow-up periods [24,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another literature review, Shah and Lutz [42] identified 139 patients treated conservatively, out of which 47% finally received surgical treatment due to absence of sustained benefit. Similarly, Hsu et al had a success rate of 55% with conservative therapy, while in another series of treatment by corticosteroid injection the long-term success rate did not exceed 57% [3,5,45]. Furthermore, most authors reporting results of conservative treatment have rather short follow-up periods [24,30].…”
Section: Discussionmentioning
confidence: 99%
“…Not all authors agree with this technique, for the fear of producing spinal instability, but in a large retrospective analysis by Lyons et al [27], no correlation between the extent of laminectomy and/or facetectomy and the development of symptomatic spondylolisthesis was identified. Trummer et al found no statistically significant difference between the type of surgical approach and the final outcome [45]. The procedure of choice should be the one that the surgeon believes will best enable complete resection of the cyst and treatment of any coinciding disease in the safest way possible, because excising the cyst seems to be the singlemost important factor for a favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their presence and potential role as a generator of symptoms must be considered. 1,2,4,5,[9][10][11][12][13][14][15][16][17][20][21][22]25 Synovial Cysts Synovial cysts are small cystic growths that occur adjacent to and attached to synovial tissue-lined joints, such as the spinal facet joints. These lesions are attached to their adjacent joints with a narrow connecting pedicle, which connects their cystic centers to the cavities of their parent joints.…”
mentioning
confidence: 99%
“…Synovial cysts may also contain hemorrhagic material because they occasionally bleed within themselves, causing acute growth and exacerbation of symptoms. 1,[4][5][6]9,10,16,20,22,[25][26][27] …”
mentioning
confidence: 99%